THE ROLE OF LEGAL AID INSTITUTIONS FOR VICTIMIZED VIOLENCE IN ACHIEVING SOCIAL JUSTICE - Wulandari, Yunita; Z, Rijal Mumazziq; Rohmah, Lailiyatur; Munawaroh, Asruril (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Justice is the rights of all Indonesian people and one of the 16th sustainable development goals, namely peace, justice and strong institutions. Especially women, the majority of whom are victims of domestic violence. The same is true for kids who have been harmed or trafficked. In Indonesia, there are numerous causes of both domestic abuse and child trafficking. The Legal Aid Institution is one of several institutions in Indonesia that deal with violence against women and children. As a result the purpose of this study is to describe and identify the role of Legal Aid Institutions in promoting justice for victims of violence, especially women as victims of domestic violence. This research is qualitative research, namely normative legal research with a statute approach. The existence of Law Number 16 of 2011 concerning Legal Aid gives The Legal Aid Institutions the freedom to provide protection for people in need. The Legal Aid Institution plays an essential role in providing justice to poor communities so that they can fight for their rights and realize the ideal of legal equality.